Dynamic simulations of hybrid energy systems in load sharing application. (5th March 2015) - Canelli, Michele; Entchev, Evgueniy; Sasso, Maurizio; Yang, Libing; Ghorab, Mohamed
Abstract: The paper analyzes the energy, environmental and economic performance of two hybrid micro-cogeneration systems in a load sharing application among residential and office buildings under Napoli (South Italy) weather conditions. The load sharing approach is investigated using dynamic simulations in comparison to a base case with separate conventional systems. Once the advantage of load sharing approach was demonstrated, the performance of two different hybrid systems in load sharing scenario were analyzed. The first one consists of a ground source heat pump (GSHP) and a fuel cell (FC); while the second one is based on a GSHP and a photovoltaic thermal (PVT) system. The performance of these two systems were also compared to a stand-alone GSHP system in order to analyze the advantages of hybrid systems to a single GSHP system. The energy analysis results show that in a load sharing case while using conventional technologies the primary energy savings are equal to 2.1% with respect to the reference case. The introduction of hybrid microcogeneration systems in load sharing application led to primary energy saving with respect to the reference case of 12.8% for the GSHP-FC system and 53.1% for the GSHP-PVT system. The environmental analysis shows a reduction of CO2 equivalent emissions equal to 15.8% and 52.0% for GSHP-FC and GSHP-PVT respectively. The better energy and environmental performance of GSHP-PVT system is due to the introduction of a significant amount of renewable energy source. The economic analysis focusses on operational cost and Simple Pay Back (SPB) index of the different cases and it is also based on an accurate study of the natural gas and electricity tariffs in Italy. This analysis highlights the advantages of the load sharing approach, because in some cases it allows the reduction of both the investment cost and the operational cost. The economic analysis for the two hybrid systems shows an operational costs reduction equal to 28.0% for GSHP-FC and 56.4% for GSHP-PVT in comparison to the reference case. In presence of economic support mechanisms, the SPB could also reach interesting values, either for the energy efficiency or for the introduction of systems based on renewable energy source. Highlights: The load sharing approach among residential and office users is analyzed. Dynamic simulations of hybrid microcogeneration systems are carried out. Performance of a hybrid ground source heat pump and fuel cell system is investigated. Performance of a hybrid ground source heat pump and photovoltaic thermal system is investigated. A thermoeconomic analysis of the different systems configuration is evaluated.